Excretion of Antibiotic Resistance Genes by Dairy Calves Fed Milk Replacers with Varying Doses of Antibiotics - Thames, Callie H.; Pruden, Amy; James, Robert E.; Ray, Partha P.; Knowlton, Katharine F. (Frontiers in Microbiology, 2012)
Elevated levels of antibiotic resistance genes (ARGs) in soil and water have been linked to livestock farms and in some cases feed antibiotics may select for antibiotic resistant gut microbiota. The purpose of this study was to examine the establishment of ARGs in the feces of calves receiving milk replacer containing no antibiotics versus subtherapeutic or therapeutic doses of tetracycline and neomycin. The effect of antibiotics on calf health was also of interest. Twenty-eight male and female dairy calves were assigned to one of the three antibiotic treatment groups at birth and fecal samples were collected at weeks 6, 7 (prior to weaning), and 12 (5 weeks after weaning). ARGs corresponding to the tetracycline (tetC, tetG, tetO, tetW, and tetX), macrolide (ermB, ermF), and sulfonamide (sul1, sul2) classes of antibiotics along with the class I integron gene, intI1, were monitored by quantitative polymerase chain reaction as potential indicators of direct selection, co-selection, or horizontal gene transfer of ARGs. Surprisingly, there was no significant effect of antibiotic treatment on the absolute abundance (gene copies per gram wet manure) of any of the ARGs except ermF, which was lower in the antibiotic-treated calf manure, presumably because a significant portion of host bacterial cells carrying ermF were not resistant to tetracycline or neomycin. However, relative abundance (gene copies normalized to 16S rRNA genes) of tetO was higher in calves fed the highest dose of antibiotic than in the other treatments. All genes, except tetC and intI1, were detectable in feces from 6 weeks onward, and tetW and tetG significantly increased (P < 0.10), even in control calves. Overall, the results provide new insight into the colonization of calf gut flora with ARGs in the early weeks. Although feed antibiotics exerted little effect on the ARGs monitored in this study, the fact that they also provided no health benefit suggests that the greater than conventional nutritional intake applied in this study overrides previously reported health benefits of antibiotics. The results suggest potential benefit of broader management strategies, and that cost and risk may be avoided by minimizing incorporation of antibiotics in milk replacer.